Does Fintech affect the psychological traits of managers? Based on the perspective of manager overconfidence - Wang, Liang; Xiao, Wenyi; Huang, Dequan (Frontiers in Psychology, 2022)
Overconfidence has undertook an indispensable role in the psychology of manager and places important significance on managers’ behavior and decision-making. This paper investigates the effect of Fintech on the psychological traits of manager from the perspective of overconfidence based on the panel data of Chinese A-share non-financial listed firms and the digital inclusive finance index of Chinese prefecture-level cities during 2011-2020. The empirical results show that: (1) Fintech exerts a negative effect on the manager overconfidence; (2) the main channels of the negative effect of Fintech on manager overconfidence include Fintech coverage breadth and Fintech usage depth; (3) For firms with severe financing constraints and lower power concentration, the negative effect of Fintech on manager overconfidence is more prominent. (4) Our benchmark results still hold after a series of robust tests, including IV regression, alter measurement of Fintech and manager overconfidence, and employ logit model re-estimation. Based on the above findings, this paper provides some insights into the cause for manager's psychological traits, keeping managers' mental health and empowering the firm's sustainable development by adopting Fintech.